Characterization of human serum spreading factor with monoclonal antibody. - Barnes, D W (1983)
Serum spreading factor is a glycoprotein isolated from human serum that promotes spreading of a variety of cell types on culture dishes. We developed mouse hybridoma lines secreting monoclonal antibody to serum spreading factor that markedly inhibited the rate of serum spreading factor-promoted spreading of both fibroblastic and epithelial cells in culture. Fibronectin-promoted cell spreading was unaffected by monoclonal antibody to serum spreading factor, and the factor appeared to be distinct by several criteria from fibronectin or laminin. Human serum-promoted cell spreading was partially inhibited by monoclonal antibody to serum spreading factor. The antibody recognized primarily two forms of serum spreading factor that migrated in NaDodSO4/polyacrylamide gel electrophoresis in a manner consistent with molecular weights of 65,000-70,000 and 75,000-78,000. In addition to being found in plasma, serum spreading factor was also found associated with washed human platelets.